2020
DOI: 10.1136/bmjopen-2019-030371
|View full text |Cite
|
Sign up to set email alerts
|

Impact of isolation on hospitalised patients who are infectious: systematic review with meta-analysis

Abstract: Strengths and limitations of this study► This review covers a wide variety of the literature from a range of different clinical areas. ► Data collected and the methods of collecting data on the impact of isolation is varied across studies. ► These data do not show if these effects are temporary, or in most cases if they are clinically significant. AbStrACtObjective To systematically review the literature exploring the impact of isolation on hospitalised patients who are infectious: psychological and non-psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
159
3
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(182 citation statements)
references
References 53 publications
8
159
3
12
Order By: Relevance
“…The present findings support previous reports suggesting several psychological perturbations and mood disturbances such as stress, depression, irritability, insomnia, fear, confusion, anger, frustration, boredom, and stigma during quarantine periods of earlier infection. 10,20,21 Regarding the COVID-19 related research, first results from Chinese studies indicate that the COVID-19 outbreak engendered anxiety, depression, sleep problems, and other psychological problems. 22,23 The significantly lower total SWEMWBS score and higher total SMFQ score "during" compared to "before" confinement support the negative effects of the current COVID-19 pandemic on mental wellbeing and emotional state in participants from Western Asian, North Africa and Europe.…”
Section: Discussionmentioning
confidence: 99%
“…The present findings support previous reports suggesting several psychological perturbations and mood disturbances such as stress, depression, irritability, insomnia, fear, confusion, anger, frustration, boredom, and stigma during quarantine periods of earlier infection. 10,20,21 Regarding the COVID-19 related research, first results from Chinese studies indicate that the COVID-19 outbreak engendered anxiety, depression, sleep problems, and other psychological problems. 22,23 The significantly lower total SWEMWBS score and higher total SMFQ score "during" compared to "before" confinement support the negative effects of the current COVID-19 pandemic on mental wellbeing and emotional state in participants from Western Asian, North Africa and Europe.…”
Section: Discussionmentioning
confidence: 99%
“…Totally, 1364 citations were considered in this review and 771 unique records were screened after removing 593 duplicate records (Figure 1). At the end of full-text screening, a total of eight reviews were included in this umbrella review (Table 2) [28,29, [40][41][42][43][44][45]. These reviews have been published between 2009 and 2020, whereas most (number of reviews, n = 5) reviews were published since 2018.…”
Section: E P U B a H E A D O F P R I N Tmentioning
confidence: 99%
“…Most reviews included cohort studies (n = 6; number/range of primary studies in each review, s = 1 to 12), followed by cross-sectional studies ( n = 5, s = 2 to 11), qualitative studies (n = 3, s = 2 to 10), case-control studies (n = 1, s = 6), quasi-experimental studies (n = 2, s = 2), case studies (n = 1, s = 2), mixed method studies (n = 1, s = 2), reviews (n = 1, s = 1), and psychological evaluation (n = 1, s = 1). In quality assessment (Supplementary material 1), three reviews were found to have high quality [28, 44,45], whereas most (n = 5) studies had a medium quality [29, [40][41][42][43].…”
Section: E P U B a H E A D O F P R I N Tmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the aforementioned benefits regarding health-care resource management and provision of emotional support, we expect psychiatry to be essential in helping to prevent and manage the higher levels of depression and worse outcomes that have been observed in patients requiring infectious isolation in hospital settings. 3 Similar to other acutely medically ill patients, those with presentations concerning for COVID-19 are likely to be vulnerable to delirium, agitation, and decompensations of psychosis or mood disorders, necessitating psychiatric evaluation. Psychiatrists will also be needed to assist with capacity evaluations for these patients should they wish to leave against medical advice.…”
Section: Letter To the Editormentioning
confidence: 99%